Denying the spoils of war : the politics of invasion and nonrecognition - O'Mahoney, Joseph P. A. (Edinburgh University Press, 2018)
Joseph O'Mahoney systematically analyses 21 case studies - including the Manchurian Crisis, the Turkish invasion of Cyprus and Russia's annexation of Crimea - to explore why so many states have adopted a policy of non-recognition of the spoils of war.